COASTAL WOMEN AS PERPETRATORS OR VICTIMS: AN ANALYSIS OF CRIMINAL PUNISHMENT AGAINST WOMEN IN CASES OF MARINE ENVIRONMENTAL DESTRUCTION IN EAST ACEH - Rika Afrida Yanti; Muhammad Natsir; Liza Agnesta Krisna (LPPM STIH Putri Maharaja, 2025)
This study examines two central issues concerning coastal women in cases of marine environmental destruction in East Aceh: (1) how environmental criminal law normatively constructs women as perpetrators, and (2) how law enforcement can incorporate substantive and restorative justice principles. Using a normative juridical method supported by analysis of legislation and judicial practice, the research finds that although the Environmental Protection and Management Law formally requires proof of fault (mens rea) for individuals, its application often remains formalistic and result-oriented. The law does not adequately differentiate between primary actors and structurally vulnerable participants, leading to the disproportionate criminalization of coastal women. The study argues that achieving genuine environmental justice requires a contextual and gender-sensitive approach, including proportional assessment of culpability and the selective application of restorative justice mechanisms. Legal reform is therefore necessary to align environmental protection with substantive justice and gender equality principles in coastal communities.